Making Purple Sweet Potato Tape Flour (Ipoema batatas var.Ayamurasaki): A Study Of FermentationTime and Yeast Concentration - Aulia Fitriani (jurnal makanan tropis dan teknologi agroindustri, 2020)
This purpose of this research to study the influence of long fermentation with yeast concentration on the quality of fermented purple sweet potato flour. This research used Random Group Design (RAK) factorial through a long fermentation consisting of 3 levels, there are U4 (4 days of fermentation), U3 (3 days of fermentation), U2 (2 days of fermentation) and yeast concentration consisting of 3 levels, there are R1 (yeast concentration 0,25%), R2 (yeast concentration 0,50%), R3 (yeast concentration 0,75%). The result of this study indicated that there was no significant interaction between long fermentation and yeast concentration in all observation variable. Long fermentation has no significant effect in all variable. Meanwhile, yeast concentration significantly affected the color of fermented purple sweet potato and the color of purple sweet potato flour. The results of best calculation are U4R3 treatment (4 days of fermentation and yeast concentration 0,75%) which show the level of water 6,45%, the level of ash 3,31%, the level of reducing sugar 34,75%, recovery 8,88%, density 0,50 (gr/ml), Lightness value 47,86, redness value 18,16, yellowness value 2,34, organoleptic aroma test 4,50 (it’s rather unusual), and organoleptic color test 5,03 (raher like it).